Relationship between Success Attributions and Academic Achievement of Secondary School Students in Anambra State, Nigeria - Obianuju Juliana, Mokwe; Adeline Nne, Anyanwu; Kingsley Ekene, Emesi (Innovare Journal of Education, 2023)
The study focused on the relationship between success attributions and academic achievement of secondary school students in Anambra State. Six research questions and six null hypotheses guided the study. Using a multi-stage sampling technique, the study adopted a correlation design with a sample size of 600 senior secondary two students drawn from the population of 11,417 co-educational students. The instrument for data collection was the Students’ Attribution Style Questionnaire. Students’ Achievement Scores were used to obtain students’ academic achievement. The reliability of the instrument was established using the Cronbach Alpha method, which yielded a reliability of .84. The Pearson Product Moment correlation was used to answer the research questions, while the t-test of the significance of the correlation was used to test the null hypotheses at a .05 level of significance. Findings from the study revealed a medium positive correlation between attributions and academic achievement scores of students with internal success attributions. Also, the finding revealed a significant relationship between attributions and academic achievement scores of students with internal success attributions. Based on these findings, it was recommended that teachers always emphasize the effort to adopt the success attribution approach in the learning process as the basis for students’ success in their academic activities and also improve the learning environment to minimize environmental constraints.